Niveles de competitividad en el Comercial Aguirre de la ciudad Babahoyo del periodo 2022. - Herrera Quinto, Vicente Joel (2023)
The competitiveness of the commercial sector in recent years has grown at the national level, in this context the commercial "Aguirre" faces several problems and strong competition within the market, it also presents low sales because they do not apply good marketing strategies that help improve the image of the company, little training for workers and the owner that allows them to know what they should implement in the company to provide better customer service and the scarcity of a marketing plan that helps the company to carry out and design better advertisements that attract attention and manage to position themselves in the minds of consumers until they make a purchase or become loyal to the company. All this has caused it to have a not very strong level of competitiveness, for which it was determined that the objective of this case study is to analyze the level of competitiveness that the company has, with the purpose of proposing a possible solution that can help the business to improve your sales and obtain greater recognition in the market. Starting from the conceptual framework, it was possible to generate arguments from the definitions of different authors that were raised and helped to carry out this case study taking into account the conceptualizations, the methods applied in this investigation were the analytical and quantitative ones that were of great help. to meet the objectives of this study. To obtain results, an interview was conducted which was addressed to the owner of the commercial where very important information was collected regarding the factors that influence the level of competitiveness in the commercial, and the surveys that were applied to the clients to to know their perspectives on the attention provided in the commercial and to know if the products and the service are to their liking. Where it was determined that the commercial has some factors that need to improve to provide a better service to customers and a low performance of competitiveness, compared to other commercial because it is lagging behind by not applying improvements in the commercial to satisfy the needs and preferences of consumers. In the conclusions the proposed and achieved objectives are stated in which it was determined that the competitive level of the company is low compared to other commercials in the market that are highly competitive, and in the recommendations the owner is given to improve the internal and external problems of the establishment, frequently provide training to the work staff, design a marketing plan that helps you create innovative and modern advertising strategies that attract the attention of people, so that they enter the premises and are interested in the products that are offered, in order to In this way, the company will be able to create an efficient corporate image, attract new clients, increase its competitive level and position within the market.